2016
DOI: 10.4038/sljb.v1i1.1
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of five toxic heavy metals in biotic and abiotic constituents of the Negombo Lagoon, Sri Lanka

Abstract: The presence of toxic metals in water has become a matter of national concern. This situation is potentially more dangerous when it occurs in lagoons and estuaries which are both highly productive and sensitive in comparison to other natural habitats. In this study, the levels of five toxic heavy metals, As, Cd, Cr, Pb and Hg, present in several abiotic and biotic constituents of the Negombo lagoon, Sri Lanka, were investigated with the objective of assessing the potential risks of accumulation. Sampling, in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…The mean tidal range on the ocean side of the inlet is 30 cm and that inside the lagoon is only 10 cm. This decrease across the inlet is due to tidal choking (Rydberg and Wickbom, 1996;Rajapaksha and Jayasiri, 2000;Sivanantha et al, 2016). The extent to which choking occurs depends on the inlet structure, freshwater supply, size of the basin, and spring neap tidal ranges.…”
Section: Driving Forces Of Eutrophication In the Negombo Lagoonmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean tidal range on the ocean side of the inlet is 30 cm and that inside the lagoon is only 10 cm. This decrease across the inlet is due to tidal choking (Rydberg and Wickbom, 1996;Rajapaksha and Jayasiri, 2000;Sivanantha et al, 2016). The extent to which choking occurs depends on the inlet structure, freshwater supply, size of the basin, and spring neap tidal ranges.…”
Section: Driving Forces Of Eutrophication In the Negombo Lagoonmentioning
confidence: 99%
“…It is worthy to note that such a short term study on this unique system may not be adequate to describe its whole scenario of Negombo lagoon and may still miss some considerations. For example, Sivanantha et al (2016) reported that most of the water discharge to the lagoon does not go through a proper purification system to reduce nutrient pollution. This high nutrient loading has contributed to a 96% decline of the standing crop of the seagrass in northern, eastern, and western parts of the Negombo Lagoon between 1997and 2004(De Silva and Amarasinghe, 2007.…”
Section: Driving Forces Of Eutrophication In the Negombo Lagoonmentioning
confidence: 99%
“…When current pollution status is taken into consideration, Kalametiya Lagoon is not at stake as the heavy metal contents did not exceed TEL and PEL. In Sri Lanka, few studies have focused on heavy metal pollution in several water bodies and lagoons including Kumbichchankulama, Alankulama, Thuruwila, dry zone and Negombo Lagoon (Bandara et al 2008;Chandrajith et al 2012;Sivanantha et al 2016). According to their results, Negombo Lagoon showed the highest content of heavy metals in the published data of Sri Lanka, for example, As: 9.89 mg/Kg; Cd: 2.63 mg/Kg; Cr: 26.1 mg/Kg ; Pb: 20.26 mg/Kg.…”
Section: Discussionmentioning
confidence: 99%